Increasing Information Seeking About Antibiotic Risks: Testing a Clinical Intervention Message Using the Risk Information Seeking and Processing Model. Issue 2 (April 2020) - Brinker, David L.; Zhou, Yanmengqian; Acevedo Callejas, Michelle L.; MacGeorge, Erina L.
We employed the risk information seeking and processing (RISP) model to inform the design of antibiotic stewardship messages aiming at influencing intentions to seek or avoid antibiotic risk information. College-age respondents ( N = 400) from a national sample viewed one of three versions of a RISP-informed message or no message (control group). Relative to the control group, all RISP-informed messages increased perceptions of information insufficiency. The most complete version of the RISP-informed message increased severity perceptions and information seeking intention and decreased information avoidance intention. Approaches to designing antibiotic stewardship messages are recommended accordingly.